Outcome of Percutaneous Coronary Intervention among Very Elderly Patients with Ischemic Heart Disease (British Journal of Multidisciplinary and Advanced Studies, 2023)
Cardiovascular disease, and ischemic heart disease (IHD), is a major cause of morbidity and mortality in the very elderly patients worldwide. These patients represent a rapidly growing cohort presenting for percutaneous coronary intervention (PCI), now constituting more than one in five patients treated with PCI in real-world practice. From July 2020 we included 152 patients with IHD purposively in Cardiology department of Bangabandhu Sheikh Mujib
Keywords: Outcome of PCI; Very elderly patients; Ischemic Heart Disease